Labour and Childbirth After Previous Caesarean Section - Reif, P.; Brezinka, C.; Fischer, T.; Husslein, P.; Lang, U.; Ramoni, A.; Zeisler, H.; Klaritsch, P. (Geburtshilfe und Frauenheilkunde, 2016)
The new expert recommendation from the Austrian Society of Obstetrics and Gynaecology (OEGGG) comprises an interpretation and summary of guidelines from the leading specialist organisations worldwide (RCOG, ACOG, SOGC, CNGOF, WHO, NIH, NICE, UpToDate). In essence it outlines alternatives to the direct pathway to elective repeat caesarean section (ERCS). In so doing it aligns with international trends, according to which a differentiated, individualised clinical approach is recommended that considers benefits and risks to both mother and child, provides detailed counselling and takes the patientʼs wishes into account. In view of good success rates (60–85 %) for vaginal birth after caesarean section (VBAC) the consideration of predictive factors during antenatal birth planning has become increasingly important. This publication provides a compact management recommendation for the majority of standard clinical situations. However it cannot and does not claim to cover all possible scenarios. The consideration of all relevant factors in each individual case, and thus the ultimate decision on mode of delivery, remains the discretion and responsibility of the treating obstetrician.
Keywords: caesarean section; status after caesarean section; vaginal delivery; management; recommendation; assessment